From Custody to Community: Outcomes of Community-Based Support for Mentally Ill Prisoners. Issue 5 (2nd September 2016) - Green, Bob; Denton, Michelle; Heffernan, Ed; Russell, Beverley; Stapleton, Larry; Waterson, Elissa
Abstract : The post-release period is associated with a range of adverse outcomes for prisoners, especially those with a mental illness. There is limited research into programmes developed to address the needs of this population upon release from custody. This paper describes the demographic, mental health and criminal justice characteristics of a cohort of 63 mentally ill prisoners referred to the Queensland Prison Mental Health Transition Coordination Program in 2010 and 2011, who received time-limited transitional support. Established criminological predictors such as age and substance abuse history were related to first re-incarceration. When a multi-event analysis was performed, a broader range of factors were associated with the time before re-incarceration, including duration of social and recovery support and a diagnosis of psychosis. This study found that among those receiving post-release social and recovery support, longer duration of support is associated with a lower risk of re-incarceration. Other findings of interest include the significant proportion of re-incarcerations for parole breaches. No deaths occurred during the follow-up period.